Candidiasis-A Fungal Infection - Cure with Homoeopathy (Homoeopathy for All, 2024)
Candidiasis is a fungal infection  caused by Candida, a yeast. Everyone  has Candida on their skin and in parts  of their body (like the mouth, throat,  gut, and vagina). Candida only  causes symptoms and infections if it  grows out of control. Vaginal candidiasis  (yeast infections) are one  of the most common fungal  infections. Candida can also  overgrow in the mouth or throat  (thrush) or in the oesophagus (the  tube leading from the throat into the  gut).
Keywords: throat; infections; Redness or soreness